Nutrition knowledge and on-field performance in women's collegiate soccer players - Cintineo, H. P.; Sutherland, K. L. (International Journal of Exercise Science Conference Proceedings, 2025)
Dietary intake is a key aspect of athletic performance and recovery between competitions. Nutrition knowledge is thought to be related to improved dietary intake in athletes, which can potentially result in enhanced athletic performance. PURPOSE: The purpose of this study was to evaluate the relationship between nutrition knowledge and on-field performance in women`s collegiate soccer players during weeks with a congested match fixture. METHODS: Ten National Collegiate Athletic Association Division I women`s soccer players (age: 18.2±6.7 y, height: 167±6 cm, mass: 63.1±7.1 kg) were included in this analysis. Athletes completed the Abridged Sports Nutrition Knowledge Questionnaire before the start of the season. Wearable sensors were worn during all soccer matches throughout the season. Data were extracted from weeks that included two matches separated by approximately 72 hours (i.e., Thursdays and Sundays). On-field performance was quantified via total distance covered (DIS) and distance covered at high speeds (>15 km/h, high-speed running [HSR]) as well as the difference between Thursday and Sunday DIS (deltaDIS) and HSR (deltaHSR). Spearman`s rank correlation was used to assess relationships between nutrition knowledge and on-field performance (a=0.05). RESULTS: The median (±IQR) nutrition knowledge score was 14.5±2.8 out of 35. Nutrition knowledge score was weakly correlated with DIS (p=0.152, p=0.674) and HSR (p=0.152, p=0.674) during Thursday matches. Further, nutrition knowledge score was weakly correlated with deltaDIS (p=-0.213, p=0.554) and moderately correlated with deltaHSR (p=-0.494, p=0.145). CONCLUSIONS: Although not statistically significant, this exploratory analysis showed higher nutrition knowledge score is moderately associated with a larger reduction in HSR from Thursday to Sunday matches. Other performance measures showed no relationship with nutrition knowledge, which can be attributed to the limited sample size in this study. However, the results may indicate institutional resources required to act upon nutrition knowledge are limited. Further, the items related to nutrition knowledge on the questionnaire may not be linked to actionable dietary intake decisions that can result in optimized athletic performance.